The Effect of 3-Month Growth Hormone Administration and 12-Month Follow-Up Duration among Heart Failure Patients Four Weeks after Myocardial Infarction: A Randomized Double-Blinded Clinical Trial - Afshin Amirpour; Mehrbod Vakhshoori; Reihaneh Zavar; Hadi Zarei; Masoumeh Sadeghi; Behzad Yavari (Hindawi-Wiley, 2021)
Background. The probable impact of growth hormone (GH) as a heart failure (HF) treatment strategy is still less investigated. Therefore, we aimed to evaluate the relation of 3-month GH prescription on left ventricular ejection fraction (LVEF), interventricular septum (IVS), posterior left ventricle (LV) thickness, end systolic and end diastolic diameters (ESD and EDD), and pulmonary arterial pressure (PAP) among Iranian individuals suffering from HF due to MI attack. Methods. A total of 16 clinically stable participants with HF diagnosis and LVEF<40% were selected for enrollment in this pilot randomized double-blinded study. They were randomly assigned equally to groups received 5 IU subcutaneous GH or placebo. Injections were done every other day for a total of 3-month duration. After termination of intervention and nine months afterwards, cardiac outcomes were assessed. Results. Baseline and 12-month posttrial participants' characteristics were similar. LVEF was increased significantly by three months started from baseline in individuals receiving GH (32±3.80% to 43.80±4.60%, P=0.002). During the next 9 months of follow-up concurrent with cessation of injections, LVEF was declined (43.80±4.60% to 32.20±6.97%, P=0.008). LVEF and ESD were remarkably higher and lower in GH group compared with controls by the end date of injections (43.80±4.60% vs. 33.14±4.84%, P=0.02 and 39.43±3.45 mm vs. 33±3.16 mm, P=0.03, respectively). No other considerable association was found in terms of other predefined variables in neither GH nor placebo groups. Conclusions. GH administration in HF patients was associated with increased LVEF function. Several randomized clinical trials are necessary proving this relation. This trial is registered with IRCT201704083035N1.